Methodology of criminal law forecasting - M. P. Kleymenov (Правоприменение, 2022)
The subject. Criminal law forecasting is a scientifically based analysis of the prospects for the development of criminal law in order to optimize criminal legislation and the practice of its application. Its subject includes: foreseeing the needs of society in the criminal law regulation of public relations, their criminalization and decriminalization; the dynamics of the development of criminal law relations in society, the development of a criminal law concept of combating socially dangerous phenomena for the foreseeable period; foreseeing the consequences of changes in criminal legislation; the presence of real prerequisites for its application; prognostic assessments of the effectiveness of criminal law norms in the process of law-making and law-realization activities; scenarios and models for the implementation of criminal law institutions and norms; technologies for combating criminality in the application of criminal law norms; prospectsfor the development of the science of criminal law itself, taking into account its scientific potential.The purpose of the article is to establish the ideology and main trends in the development of criminal legislation and the practice of its application in post-Soviet Russia, to determine the methodology for the modernization of criminal policy in the new geopolitical conditions.The methodology of research includes axiological and system approaches, determinative analysis, search and normative forecasting, extrapolation, expert assessments, modeling.The main results, scope of application. There are two diametrically opposed ideologies that are of fundamental importance for criminal law and criminal law forecasting: 1) liberal and 2) conservative. The criminal law policy of the Russian Federation has so far developed in line with liberal ideology. Its main goal is to modernize criminal legislation in terms of decriminalizing economic crimes and humanizing the treatment of white-collar criminals. Conservative criminal law policy is based on the methodology of normative forecasting, which is aimed at achieving the desired (for the state and society) results. This methodology is based on a systematic approach. From the standpoint of this approach, the object of criminal law forecasting is an organized system with an extremely complex structure consisting of three subsystems: managing, managed and criminal law norms. The content of each of these subsystems requires corrective action in order to achieve compliance with the traditional axiological scale and common sense. It is also necessary to solve the problem of coordinating criminal law and criminological legislation.Conclusions. Criminal law forecasting allows us to formulate a number of theses that should be the basis for the concept of optimizing the criminal policy of the Russian Federation: (a) rejection of the liberal model of criminal law regulation of public relations, the transition to a conservative model, which should be dominated by state and public, not private interests; (b) recognition of organized economic and official crime as priority objects of criminallegal influence; (c) coordination of criminal-legal and criminological legislation; (d) adoption of the Federal Law "On Combating Organized Crime".